Enabling sustainable project management in pakistani construction industry : the influence of institutional pressures and moderating role of transformational leadership - Mehfooz, Ullah (2021)
Sustainable corporate practices are gaining ever-increasing attention in the contemporary business world and integrating sustainability aspects in project management is an emerging trend across the mainstream industries, particularly in construction. This approach is often termed as Sustainable Project Management (SPM) which is considered a new school of thought in the field of project management. However, sustainability research in the project context is fragmented and still at a nascent stage with lesser attention directed towards the key external and internal enablers of SPM particularly in construction industry of developing countries. The aim of this study is thus, to address this research gap by empirically developing and testing a model for the enablers of SPM in construction industry. Based on an extensive literature review, five research questions were proposed for this study to address current gaps in the body of knowledge. Using institutional theory as a basic frame of reference, this study proposed three isomorphic pressures i.e. coercive, normative and mimetic pressures as external enablers for integrating sustainability in project management. This study also included transformational leadership qualities of portfolio managers as moderating variable on the relationship of isomorphic pressures and SPM. An online survey was administrated to gather data from large constructor firms in Pakistan with project managers as key respondents. 146 large constructor firms recorded their responses which were then analyzed using structural equation modelling (SEM) technique in Smart PLS software. The findings showed that the three isomorphic pressures significantly predict the adoption of SPM by construction firms, with mimetic isomorphism being the higher performer. The presence of transformational leadership qualities at portfolio management level strengthens the influence of isomorphism on SPM adoption. Results of the first and second level measurement model assessments affirmed that constructor firms do practice SPM to certain degree but their practices are not standardized. In fact, environmental dimension overrides the whole concept of SPM in terms of practice and social sustainability receive lesser attention. Theoretically, this study provides a model that combines the internal and external enablers of SPM based on institutional theory and transformational leadership theory. The empirical findings of the study validated the robustness of the proposed framework to study the SPM implementation in construction industry. Finally, this study offers practical suggestions for practitioners and policy makers. The inferred implications suggest that constructor firms need to approach isomorphism with a proactive approach, rather being reactive to regulations, and should include sustainability criteria in strategic decision making. This will help them gaining a long-term competitive advantage and will create a win-win situation where constructor firms will be a part of the solution towards achieving the broader goals of overall sustainable development.